BANTAL SIU PADA UPACARA PAWIWAHAN DI KELURAHAN BALER BALE AGUNG KECAMATAN NEGARA KABUPATEN JEMBRANA - I Gusti Ayu Ngurah; Ni Ketut Caturadi Mahyuni (FAKULTAS ILMU AGAMA DAN KEBUDAYAAN, 2020)
This article discusses of bantal siu at a ceremony in Baler Bale Agung Village, Negara District of Jembrana Regency. Banten is unique and different from other regions, but still refers to the teachings of Hinduism. The topic that will be studied is about the shape and function of the bantal siu at a pawiwahan ceremony. This research is qualitative, data collection is done by field interviews, document studies and observations. From the analysis of the results of the data, the research results obtained are: 1) The shape of the Banten Bantal Siu is used in the Baler Bale Agung Village in the procession of the bride and groom carrying out the nutmeg. 2) Banten Bantal Siu several functions are have, namely: religious function, social function, aesthetic function, and education function.